Keabsahan Dan Kekuatan Pembuktian Akta Notaris: Perspektif Cyber Notary Di Indonesia - Fabela Rahma Monetery; Budi Santoso (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2023)
AbstractCyber notary implies notarial deed made through electronic device or notary, agreement that reads and knows deed isn’t carried out before notary. This writing aims to analyze validity of authentic deed transaction certification carried out with cyber notary and strength of notary deed proof in concept implementing cyber notary in Indonesia. Researchers use legal research methods using normative juridical approach, namely the concept of positivist legis. The certification transactions using cyber notary is legal, it has been regulated in Article 15 paragraph (3) of Law Number 2 of 2014 which authorizes notary to certify transactions in cyber notary manner while still taking into account the elements of an authentic document. Notary document that based on cyber notary in form of an electronic or electronic document, doesn’t or has not fulfilled the conditions as a valid document based on the Act on Changes Notary Position or Law on Information and Electronic Transactions. Thus, power of proof is the same as power of proof letter or document made under the hand. Therefore, preserve the authenticity of deed electronically made using draft of cyber notary that have perfection.Keywords: validity; evidence; cyber notaryAbstrakCyber notary memiliki definisi bahwasanya akta notaris yang diterbitkan menggunakan perangkat elektronik atau seorang Notaris cuma memvalidasi sebuah perjanjian dimana pembacaan serta penandatanganan aktanya tidaklah dikerjakan di depan Notaris. Artikel ini bertujuan untuk menganalisis keabsahan sertifikasi transaksi akta otentik yang dilakukan dengan “cyber notary” dan kekuatan pembuktian akta Notaris pada konsep implementasi “cyber notary” di Indonesia. Artikel ini menggunakan metode yuridis normatif. Pensertifikatan transaksi yang memakai cyber notary merupakan hal yang legal sebagaimana diatur di Pasal 15 ayat (3) Undang-undang Nomor 2 Tahun 2014 yang memberi wewenang pada notaris dalam menerapkan pensertifikasian transaksi dengan cara “cyber notary” tanpa mengabaikan unsur akta asli. Akta Notaris yang didasarkan pada konsep “cyber notary” berupa akta elektronik atau elektronik, tidak atau belum memenuhi persyaratan sebagai akta otentik menurut perundang-undangan Perubahan wewenang Notaris atau perundang-undangan Informasi dan Transaksi Elektronik. Kekuatan pembuktian sama kuatnya dengan suatu surat atau akta yang diteken di bawah tangan. Hal tersebut untuk menjaga keaslian akta yang dibuat secara elektronik melalui konsep cyber notary yang memiliki kesempurnaan.Kata kunci: keabsahan; pembuktian; cyber notary